2012
DOI: 10.1016/j.febslet.2012.07.015
|View full text |Cite
|
Sign up to set email alerts
|

PC‐PLC is involved in osteoclastogenesis induced by TNF‐α through upregulating IP3R1 expression

Abstract: a b s t r a c tThe precise mechanism of how TNF-a promotes osteoclast formation is not clear. Previous reports show TNF-a targets molecules that regulate calcium signaling. Inositol-1,4,5-trisphosphate receptors (IP3Rs) are important calcium channel responsible for evoking intracellular calcium oscillation. We found that TNF-a increased the expression of IP3R1 and promoted osteoclastogenesis in RANKLinduced mouse BMMs. Phosphatidylcholine-specific phospholipase C (PC-PLC) specific inhibitor D609 eliminated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…In addition to direct actions on osteoclasts and their precursors, TNF-α may indirectly promote osteoclast activity through induction of expression of both RANKL and M-CSF in osteoblasts and marrow stromal cells [21,36,41] . Last but not least, TNF-α increases the expression of IP3R1, an important calcium channel responsible for evoking intracellular calcium oscillation, which promotes RANKL-induced osteoclastogenesis of mouse BMMs [42] . This scenario may explain why the increase in proinflammatory cytokines induced by prosthetic wear particles strongly enhances osteoclast formation and bone resorption in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to direct actions on osteoclasts and their precursors, TNF-α may indirectly promote osteoclast activity through induction of expression of both RANKL and M-CSF in osteoblasts and marrow stromal cells [21,36,41] . Last but not least, TNF-α increases the expression of IP3R1, an important calcium channel responsible for evoking intracellular calcium oscillation, which promotes RANKL-induced osteoclastogenesis of mouse BMMs [42] . This scenario may explain why the increase in proinflammatory cytokines induced by prosthetic wear particles strongly enhances osteoclast formation and bone resorption in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Besides acting on PC-PLC, this molecule was also reported to affect PLD activity and to inhibit sphingomyelin synthase in some cell types [156]. However, strong evidence for a specific inhibitory effect of D609 on PC-PLC was provided in our previous studies [62,65,68,69,157], as well as by other groups [158][159][160]. Mellert et al [161] studied the effect of this drug on HIV-1 infection, showing that a D609/undecanoic acid combination inhibited HIV-1 replication in infected lymphoma cells, likely interfering with virus assembly.…”
Section: Plcs In Hiv-1 Infectionmentioning
confidence: 89%
“…It was found that TNF-α promoted RANKL-induced osteoclastogenesis, at least partially, through the PC-PLC/inositol-1,4,5-trisphosphate (IP 3 ) receptors/NFAT1 pathway [333]. …”
Section: Non-specific Phospholipase Cmentioning
confidence: 99%